Penerapan Pembelajaran Realistic Mathematics Education dengan Strategi Means Ends Analysis untuk Meningkatkan Kemampuan Berpikir Kritis - Helen Utarni; Fauzi Mulyatna (Institut Agama Islam Negeri Curup, 2020)
This research is an effort to improve students' critical thinking ability by applying Realistic Mathematics Education (RME) learning with Means Ends Analysis (MEA) strategy. The method used in this research is classroom action research in 2 cycles. Each cycle passes through 4 stages; they are planning, implementation, observation, and reflection. The learning process in class X IPS-3 for each cycle uses RME approach with MEA strategy. Students are given an essay test at each end of the cycle to measure their critical thinking abilities. Conclusion shows that students’ critical thinking ability increases from 56% (cycle I) to 84% (cycle II) by applying RME approach with MEA strategy.